Biliary cirrhosis in a child with inherited interleukin-12 deficiency. - Pulickal, A; Hambleton, S; Callaghan, M; Moore, C; Goulding, J; Goodsall, A; Baretto, R; Lammas, D; Anderson, S; Levin, M; Pollard, A (2008)
Interleukin-12 (IL-12) is a key cytokine in the defense against intracellular bacteria notably Mycobacteria and Salmonella species. We report a case of disseminated mycobacterial infection, following BCG vaccination, in a child who later developed tuberculosis. Functional tests and a novel diagnostic polymerase chain reaction (PCR) assay, revealed a loss-of-function deletion in the IL12 gene. Analysis of samples from the parents and siblings of the patient indicated an autosomal recessive inheritance pattern with varying degrees of phenotypic expression in identical genotypes. Interferon-gamma (IFN-gamma) therapy was associated with marked clinical improvement. Biliary cirrhosis, a hitherto unreported complication of IL-12 deficiency, developed later and required liver transplantation. A defect in the IL-12-IFN-gamma pathway should be suspected in patients presenting with multiple, repeated or persistent infection with intracellular bacteria. The diagnostic work-up and the immuno-genetic assay described here can aid in the quick and reliable diagnosis of IL-12 deficiency resulting from genetic defects and its subsequent management.